Analysis of the Influence of the Missouri Mathematics Project Learning Model on Elementary Students' Mathematical Connection Skills and Habits of Mind - Khofifah Amaliyatul Maula; Ananta Jelita Putri Ayu (MIREJ: Multidisciplinary Innovation Research Journal, 2026)
This study examined the effect of the Missouri Mathematics Project (MMP) on elementary school students' mathematical connection ability and habits of mind. A quantitative study employing a quasi-experimental pretest-posttest control group design involved fifth-grade elementary school students. Data were collected using a mathematical connection test and a habits of mind questionnaire. The data were analyzed using descriptive statistics and Multivariate Analysis of Variance (MANOVA) after satisfying the assumptions of normality and homogeneity. The findings revealed that students who learned through MMP obtained higher mean scores in both mathematical connection ability and habits of mind than those who received conventional instruction. The MANOVA results indicated that the differences were not statistically significant for mathematical connection ability (p = 0.314) or habits of mind (p = 0.110). These findings suggest that although the structured learning stages of MMP encouraged students to engage in problem-solving activities, review prior knowledge, and practice mathematical procedures systematically, the intervention duration was insufficient to produce significant improvements in students' mathematical connection ability and thinking dispositions. The value of this study lies in providing empirical evidence that the effectiveness of MMP should be interpreted by considering contextual factors, including students' initial mathematical competence, instructional duration, and classroom learning conditions, rather than relying solely on score improvement. The study concludes that MMP has the potential to support the development of mathematical connections and productive thinking habits; however, longer implementation periods and complementary instructional strategies are required to achieve statistically significant learning gains in elementary mathematics education.